GERONTEOLOGI PANTEKOSTA: Manusia Lanjut Usia sebagai Subjek Diakonia Sosial - Elia Tambunan (DIEGESIS: Jurnal Teologi Kharismatika, 2023)
Indisputable, by remembering Pantecost, the association formed in the minds of academics is the doctrinal "drama" of the church that is infatuated with the strange manifestations of the Holy Spirit. Not many have considered that there is an academic reason to say, in the capacity possessed by Pentecostals according to their respective zones, they contribute socially to local communities. This paper answers how to humanize humans. With qualitative research by reading Pentecostal literature as a primary source, and interviewing many pastors, it is clear that the empirical data is true that there is Pantecostal gerontheology. Until now, these people are struggling to make adults the subject of social diakonia. Pantecostals represents the church's social responsibility to humans which is rightly seen as one of the social ways the church is present in the public arena so that they live a more dignified life.Keywords: Social Diakonia; Gerontheology; Elders; Pantecost.Â AbstrakSulit untuk dibantah, dengan hanya mengingat Pantekosta, maka asosiasi yang terbentuk di nalar akademisi ialah â€œdramaâ€ doktrinal gereja yang tergila-gila dengan manifestasi Roh Kudus yang ganjil. Tak banyak yang memperhatikan ada alasan akademis untuk mengatakan, dalam kapasitas yang dimiliki oleh kaum Pantekosta sesuai dengan zona masing-masing, mereka berkontribusi sosial kepada masyarakat lokal. Tulisan ini menjawab bagaimana memanusiakan manusia usia lanjut? Dengan penelitian kualitatif lewat membaca literatur Pantekosta sebagai sumber primer, dan mewancarai sejumlah pendeta terlihat data empiris benar ada geronteologi Pantekosta. Hingga sekarang, kaum ini terus bergulat untuk menjadikan orang dewasa sebagai subjek diakonia sosial. Pantekosta merepresentasikan tanggung jawab sosial gereja kepada manusia yang tepat dilihat sebagai salah satu cara sosial menggereja hadir di arena publik agar mereka hidup lebih bermartabat.Kata kunci: Diakonia Sosial; Geronteologi; Manula; Pantekosta.